Attitudes and beliefs toward biobehavioural research participation: voices and concerns of urban adolescent females receiving outpatient mental health treatment. (November 2013) - Brawner, Bridgette M.; Volpe, Ellen M.; Stewart, Jennifer M.; Gomes, Melissa M.
Abstract Background: Biobehavioural research methodology can be invasive and burdensome for participants – particularly adolescents with mental illnesses. Human biological researchers should consider how methodological impositions may hinder adolescent research participation. However, literature on adolescent's voices and concerns toward biobehavioural research participation is virtually non-existent. Aim: This study was designed to determine adolescents' perceptions of participation in research involving the collection of biomarkers via blood, saliva and/or urine samples. Subjects and methods: Urban adolescent females (aged 12–19) receiving outpatient mental health treatment (n = 37) participated in focus groups with concurrent survey administration to explore attitudes, beliefs and willingness/intentions toward biobehavioural research participation. Results: Participants had favourable attitudes toward biobehavioural research and were amenable to provide each specimen type. Mistrust for research emerged, however, and concerns related to privacy and confidentiality were expressed. Conclusion: Participant recruitment is a critical component in study design and implementation; this includes knowledge of population-specific recruitment barriers and facilitators. This innovative paper provides a context for the research participants' decision-making process, strategies to allay fears and concerns and concrete areas to target in research-related interventions. Although the findings are from a specific, US-based sample, the implications warrant replication of the research in other geosocial settings.